Modalidad de ejecución y variabilidad del costo de inversión de obras de la Municipalidad Provincial de Alto Amazonas, distrito de Yurimaguas, 2010-2014 - Alcalde Rodríguez, Ani (2002)
The final report thesis entitled "Method of execution and variability investment cost of works of the Provincial Municipality of Alto Amazonas Yurimaguas district, 2010-2014," was the main problem Is there a relationship between the implementation modality and variability the investment cost of works of the Provincial Municipality of Alto Amazonas Yurimaguas district, period 2010-2014 to enable the viability of public works for the population? And whose overall objective was to determine the relationship between mode of execution and variability investment cost of works of the Provincial Municipality of Alto Amazonas Yurimaguas district, 2010-2014. The study worked with a type of non-experimental research, with a descriptive and correlational descriptive design level. The population sample corresponded to all information obtained from the studied variables (execution mode and variability investment cost of works) of the Provincial Municipality of Alto Amazonas in the periods 2010, 2011, 2012, 2013 and 2014; using as research tools two guides Summary tab. In the development of research we worked with three modes of execution of works: mixed, direct and contract administration. The mixed mode had a total of 6 projects in the years studied, direct administration modality had 25 projects and contract modality had 63 projects over the past five years. Giving a total of 94 projects carried out in the district of Yurimaguas for three municipal governments. He was from 2010 to 2014 variabilities up to 3 million by 40%, 3 million one thousand-up to 6 million with 30% and works with a value of 6 million one thousand more with variability of 20%. Works with greater variability than 20% are 2; works with 40% greater variability are 3 and works with 30% greater variability are 9. All of them give a total of 14 works with variations greater than those indicated by the SNIP spending. Finally in hiring hypothesis we worked with a significance level of 5%, which was 2.37 Ft while the Fc was greater with a value of 4,095. Therefore hiring the hypothesis indicated that there is a 95% acceptance of the alternative hypothesis, so the Hi accepted: There is a relationship between the implementation modality and variability of the investment cost of works in the Provincial Municipality of Alto Amazonas, Yurimaguas district, 2010-2014